IL-1 and LPS but not IL-6 inhibit differentiation and downregulate PPAR gamma in brown adipocytes - Mrácek, Tomás; Cannon, Barbara; Houstek, Josef (Cytokine, 2004)
Brown adipose tissue (BAT) is well recognized as a heat-producing organ of rodents and generally all young mammals. There is good experimental evidence that its thermogenic activity plays a role also during development of fever and that this activation is mediated exclusively via an adrenergic pathway. However, we have shown that brown adipocytes highly express receptors for pyrogenic factors (IL-1, LPS) and that after their activation, brown adipocytes are capable of responding by production of IL-6 and IL-1alpha. In this study we examined the effect of chronic treatment of mouse brown adipocytes in primary culture with pyrogens (IL-1beta, IL-6 and LPS) on their ability to differentiate into mature adipocytes. We found that treatment with IL-1beta or LPS, but not with IL-6, inhibited the differentiation of brown adipocytes, which was accompanied by a 2.5-10-fold decrease in PPARgamma mRNA. The anti-adipogenic effect of IL-1beta and LPS could thus be mediated via downregulation of PPARgamma levels, similar to the anti-adipogenic action of another pyrogenic cytokine--TNFalpha. We also found that pretreatment of brown adipocytes with IL-1beta or LPS led to a more pronounced (2-4-fold) induction of IL-6 transcripts upon whole 24h time course of adrenergic stimulation. These results support the view that BAT functions not only as an effector but also as a mediator of the febrile response; while the thermogenic activity is associated with terminally differentiated cells, earlier developmental states of brown adipocytes seem to be able to play a mediatory role.
Keywords: buněčná diferenciace; messenger RNA; lipopolysacharidy; Down-Regulation; Lipopolysaccharides; Interleukin-6; zvířata; Cells, Cultured; myši; Norepinephrine; down regulace; Mice; hnědá tuková tkáň; RNA, Messenger; interleukin-6; kultivované buňky; Cell Differentiation; noradrenalin; Animals; Interleukin-1; Adipose Tissue, Brown; interleukin-1